'What you look like is such a big factor': Girls' own reflections about the appearance culture in an all-girls' school - Carey, Renee; Donaghue, N.; Broderick, P. (2011)
High school is a key venue for the development and expression of body image concerns in adolescent girls. Researchers have begun to investigate the role of school-based 'appearance cultures' in magnifying the body image concerns of students. To date, however, no research has examined girls' experience as participants within these cultures, and thus the opportunity to learn how girls account for the development and maintenance of these cultures has been missed. In interviews with nine girls attending an all-girls' school, the existence of a strong 'appearance culture' in the school was identified as a major influence on the body image concerns of students. Girls talked about the ways in which appearance-focused conversations, dieting, and weight monitoring occurred as part of the everyday interaction with friends and peers at school. They also identified many ways in which their school attempted to address body image concerns, although these attempts were often portrayed as ineffective, if not counter-productive. These findings suggest that attempts to address the body image concerns of students will need to be sensitive to the lived reality of appearance cultures within schools. © The Author(s) 2010.